ANALYSIS OF MARKETING INFORMATION SYSTEMS AND CONCEPTION OF AN INTEGRATED MARKETING INFORMATION SYSTEM - Nedeva, Veselina Ivanova (International Journal of Computing, 2014)
The article presents the results of a research in the field of the marketing information technologies. The subjects of the research are the marketing information systems, mainly the information systems used in the marketing business activities of the studied companies. 25 marketing information systems were covered. Data were collected in the period 1999-2002. A study was conducted on the basis of criteria and indices preliminarily worked out as well. Analysis was made, results were obtained and a concept for the building of a marketing information system of an integrated kind was proposed.